Necessity of applying the concept of the steady state on the numerical analyses of excavation issues: laboratory, field and numerical investigations. Issue 2 (4th March 2022) - Heidarzadeh, Heisam; Kamgar, Reza
ABSTRACT: This research consists of two main parts. First, some laboratory and field tests have been conducted on a specific soil. Therefore, a series of laboratory and field data have been obtained that can be used to evaluate numerical analyses. In the second part, an elastoplastic constitutive model is introduced based on Duncan-Chang constitutive model. The steady state concept has been added to this constitutive model using the state parameter. The mentioned constitutive models have been calibrated using laboratory data for the soil. Then, these constitutive models have been applied in the numerical analysis of an excavation problem monitored during construction. Thus, the effect of the state parameter and steady-state concept on the numerical results has been evaluated with a comparison between the numerical analyses and field observation. Finally, according to the numerical analyses and field data, it has been concluded that the steady state concept in constitutive models can play a significant role to improve the numerical simulations of geotechnical structures.